Predictors of mid-term outcomes in 334 developmental dysplasia hips treated with total hip arthroplasty - Cheng-Qi Jia; Mei Gao; Yu-Jie Wu; Hong-Fa Pan; Kan Liu (BMC Musculoskeletal Disorders)
Abstract Aims Under the trend of gradual morphological evolution of different types of developmental dysplasia of the hip (DDH), this study aimed to investigate objective factors to predict complications in DDH patients after total hip arthroplasty (THA). Methods From July 2010 to December 2019, 241 DDH patients (334 hips) received THA. The minimum follow-up time was five years. Univariable and multivariable logistic regression analyses were used to determine predictors of complications. Results The incidence of periprosthetic fractures was 1.5% and BMI was independently associated with it (odds ratio [OR]: 0.698; 95% confidence interval [CI]: 0.505–0.966); acetabular prosthesis position was independently associated with limp (34.1%) (OR: 2.369; 95% CI: 1.267–4.432); height (OR: 0.003; 95% CI: 0.000-0.579), short left leg (OR: 0.203; 95% CI: 0.066–0.621) and femoral prosthesis distal size (OR: 0.778; 95% CI: 0.617–0.981) were associated with knee valgus (19.5%); limb length discrepancy (OR: 1.378; 95% CI: 1.034–1.835) and femoral head size (OR: 1.329; 95% CI: 1.053–1.678) were associated with knee pain (2.4%); femoral prosthesis (S-Rom) (OR: 0.045; 95% CI: 0.004–0.507) and acetabular prosthesis position (OR: 23.381; 95% CI: 1.297–421.580) were associated with thigh pain (distal femoral prosthesis) (2.1%); femoral prosthesis was associated with hip abnormal noise (5.4%) (S-Rom: OR: 0.034; 95% CI: 0.004–0.313; Corail: OR: 0.077; 95% CI: 0.008–0.726). Conclusion Tall, higher BMI, short left leg, lower limb length discrepancy, anatomical acetabulum, friendly femoral prosthesis, smaller femoral head size, or larger femoral prosthesis distal size were found to have lower complications, but the preoperative Crowe type was not confirmed as a risk factor.